UJI SENYAWA FLAVONOID TOTAL DARI EKSTRAK ETANOL HERBA BINARA (ARTEMISIA ANNUA) MENGGUNAKAN HIGH PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC) TAHUN 2019 - Purba, Novandi; Sinurat, Jhon Patar; Marbun, Romauli Anna Teresia (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2019)
ABSTRAK Herba binara (Artemisia Annua) is one of the plants that contains flavonoids which are efficacious as antioxidants and anticancer. The purpose of this study was to determine the total flavonoid compounds contained in ethanol extract of binara herbs (Artemisia Annua). Compounds in ethanol extract of binara herbs were identified by phytochemical screening. The results showed that the ethanol extract of binara herbs contained alkaloids, flavonoids, saponins, and tannins. Extraction was carried out in two stages, namely maceration stage with 96% ethanol and fat removal stage by hydrolysis using distilled water solvent. The extract was partitioned with ethyl acetate and n-hexane solvents, then the partitions were examined by TLC using the mobile phase of chloroform and ethyl acetate (7: 3). Ribbon patches that have the same Rf and color prices as the initial detection are taken and searched. Then analyzed using High Performance Liquid Chromatography (HPLC). Based on the wavelength as well as the TLC test, a partial structure which was strongly suspected of total flavonoids was 0.93 g. Kata Kunci :Herba Binara (Artemisia Annua), flavonoid, KLT, High Performance Liquid Chromatography(HPLC).